Dietary intervention strategies for ethnic Chinese women with gestational diabetes mellitus: A systematic review and meta‐analysis. Issue 2 (1st April 2019) - Wan, Ching S.; Nankervis, Alison; Teede, Helena; Aroni, Rosalie
Abstract : Aim: Ethnic Chinese women are one of the populations at high risk of gestational diabetes mellitus (GDM) internationally. This systematic review aimed to determine which dietary intervention strategies were found to be effective in improving glycaemic control and pregnancy outcomes among ethnic Chinese women with GDM. Methods: The review protocol was registered with PROSPERO (CRD42016043585). Eight English and four Chinese language databases were searched for randomised controlled trials and cohort studies of dietary intervention among ethnic Chinese women with GDM. Review Manager 5.3 and GRADE criteria were used in meta‐analysis and assessment of quality of evidence. Results: Included studies comprised 3944 women in 29 eligible studies. Compared to standard treatment, low glycaemic index (GI) diets, low glycaemic load (GL) diets and fibre‐enriched diets were associated with a reduction in fasting plasma glucose, 2‐hour plasma glucose and HbA1c, and improved neonatal outcomes. Low GL diets were associated with reduced caesarean section risk. Conclusions: In ethnic Chinese women with GDM, low GI diets, low GL diets and fibre‐enriched diets were associated with improved glycaemic control and pregnancy outcomes. Given the lack of direct comparison of these three diets, future direct comparison trials are necessary to determine optimal dietary intervention strategies.